The Relationship Between Nutritional Status with Post Dural Puncture Headache Incident in Sectio Caesarea Patients with Spinal Anesthesi - Agussalim Ali (MEDULA JURNAL ILMIAH FAKULLTAS KEDOKTERAN UNIVERSITAS HALU OLEO, 2022)
Background: Post dural puncture headache (PDPH) is one of the most common complications of spinal anesthesia caused by leakage of cerebrospinal fluid (CSS) after anesthesia procedures. One of the factors that influence the incidence of PDPH is nutrional status where obese patients tend not to experience PDPH. This is based on an increase intraabdominal pressure in obese patients which can reduce CSF leakage in the epidural space. Purpose: Purpose of this study to determine whether there was a relationship between nutritional status and post dural puncture headache incident in sectio caesarea patients with spinal anesthesia at Aliyah 2 Hospital. Methods: This study used an observational analytic study with a cross sectional approach carried out at Aliyah 2 Hospital. The number of samples in this study was 51 people who were taken using total sampling technique. Data collection was obtained from medical records and filling out observation sheets for post-sectio caesarea patients with spinal anesthesia and then analyzed using the Fisher’s Exact Test. The dependent variable in this study was PDPH and the independent variables was the nutrional status. Result: This study showed that nutritional status (p = 0.007) had a significant relationship with the incidence of PDPH at Aliyah Hospital 2. Conclusion: From this study it could be concluded that the incidence of PDPH  after spinal anasthesia is higher in patients with low BMI.